Discovery of the life cycle of Sarcocystis lacerine Babudieri, 1932 (Apicomplexa: Sarcocystidae), with a species redescription - Volf, Jiří; Modrý, David; Koudela, Břetislav; Šlapeta, Jan R.
Oocysts/sporocysts of Sarcocystis sp. were found in the intestinal contents of the smooth snake, Coronella austriaca I .aurenti. Common voles Microtus arvalis (Pallas), bank voles Clethrionomys glareolus (Schreber), green lizards Lacerta viridis (Laurcnti), and common wall lizards Podarcis muralis (Laurenti) were experimentally inoculated as potential intermediate hosts. Only common wall lizards were found to be susceptible intermediate hosts. Transparent, macroscopically hardly visible sarcocysts found in tail striated muscles of lizards were 480 (390-640) x 210 (190-230) pm in size 72 days post-infection. Using the light microscopy, the sarcocyst wall was about 1 pm thick with an apparent layer of villi approx. 2 pm thick. Ullraslruclurally, the primary cyst wall was characterised by spine-like villar protrusions up to 2.5 pm in length and 0.5 pm in diameter. Based on sarcocyst morphology and experimental data, the discovered Sarcocystis species is suggested to be conspccific with Sarcocystis lacertae Babudieri, 1932. A redescription of Sarcocystis lacertae is presented in this study.